The Influence of Public Service Quality in the Health Sector on Public Satisfaction at the Lateri Village Community Health Center, Baguala District, Ambon City - Elisabet Saurma Sidabutar; Zainal Abidin Rengifurwarin; Pieter Sammy Soselisa (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to analyze the effect of public service quality in the health sector on community satisfaction as service users at the Lateri Village Community Health Center, Baguala District, Ambon City. From a public administration perspective, healthcare services are positioned as an integral part of public service delivery, which constitutes the government’s responsibility in fulfilling citizens’ basic rights and in promoting responsive and accountable governance. Methodology: A quantitative explanatory design was employed using simple linear regression analysis. Data were collected from 80 service users through a structured questionnaire based on a five-point Likert scale. Service quality indicators were adapted from established healthcare quality frameworks and reinterpreted within a public service governance perspective. Statistical analysis was conducted using SPSS after validity, reliability, and classical assumption testing. Main Findings: The findings indicate that public healthcare service quality has a positive and significant effect on community satisfaction. Improvements in accessibility, efficiency, humane interaction, and service reliability contribute to more favorable citizen evaluations of public service performance. These results suggest that service quality functions not only as an operational standard but also as a governance mechanism that shapes public trust and institutional legitimacy at the local level. Novelty/Originality of this study: This study provides empirical contributions to the development of public administration by integrating health service quality dimensions into a public service analysis framework. It enriches the social science literature, particularly in the study of public service quality and community satisfaction in primary healthcare services. Furthermore, the study offers practical implications for improving the performance of public sector organizations, especially Community Health Centers (Puskesmas) as public service providers in eastern Indonesia.